Conversor SEPIC quadrático não isolado sem capacitores eletrolíticos para acionamento de iluminação a LED - Corrêa, Douglas Rosa (2020)
This work presents an ac-dc quadratic SEPIC converter that performs input power factor correction (PFC) used as a driver in lighting applications involving light emitting diodes (LEDs). This structure provides wide conversion rate and is capable of operating in voltage step-up and step-down modes. Considering that the useful life of LEDs is much longer than that of electrolytic capacitors, the converter employs only film capacitors. The integration of two SEPIC converters using the graft scheme allows the first stage to provide PFC and the second stage to perform power control (PC) with a single active switch. A detailed mathematical study is presented through a qualitative and quantitative analysis in order to obtain the design procedure comprising all elements of the topology. Simulation and experimental results are presented, thus demonstrating the advantages and disadvantages of the structure and validating the theoretical assumptions.